Analisis Komparasi Kinerja Keuangan Perusahaan Food and Beverage di BEI Sebelum dan Selama Pandemi Covid-19 - Fridariani, Ni Made; Dana, I Made (E-Jurnal Akuntansi, 2023)
Financial performance has an important role in a company. Financial performance is an indicator to find out whether the company will continue to run well or not in the future. The research aims to analyze differences in the financial performance of food and beverage companies before and during the Covid-19 pandemic on the Indonesia Stock Exchange for the 2018-2021 period. The sample was determined using the census sampling method. The number of samples used was 26 companies. The analysis technique used is the Wilcoxon Signed Rank Test. The research results showed that there were no differences in the liquidity ratio, solvency ratio, profitability ratio and market valuation ratio in financial performance before and during the Covid-19 pandemic, while in the activity ratio there was a difference in financial performance before and during the Covid-19 pandemic. Keywords: Covid-19 Pandemic; Financial Performance; Financial Ratios